(untitled) (International Journal of Plant Biology, 2020)
Ultraviolet (UV) is a component of the solar radiation with a wavelength in the range of 100 ≤ λ ≤ 390 nm that is almost entirely shielded by the terrestrial atmosphere, but not in space. The effects of UV-C (100 ≤ λ ≤ 280 nm) on plants mainly depend on: i) the applied UV-C radiation dose and quality, ii) the different plant species and varieties used, and iii) the phenological phase of irradiated plants. UV-C radiation can be extremely dangerous also at low exposition times. On the other side, considering that terrestrial plants under sunlight are naturally exposed to low doses of UV-C, the question is how much UV-C could be beneficial for plants cultivated in space, in relation to i) protection of plants from pathogens, ii) increase of the concentration of important dietary supplements, and iii) regulation of some physiological processes. The research on UV-C should be more addressed to better evaluate the damages and benefits in UV-C-exposed photosynthetic organisms, involving plants useful for Bioregenerative Life Support Systems (BLSSs).